2018
DOI: 10.1159/000494665
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Calcification in Hemodialysis and Peritoneal Dialysis

Abstract: Background: Vascular calcification is seen in most patients on dialysis and is strongly associated with cardiovascular mortality. Vascular calcification is promoted by phosphate, which generally reaches higher levels in hemodialysis than in peritoneal dialysis. However, whether vascular calcification develops less in peritoneal dialysis than in hemodialysis is currently unknown. Therefore, we compared coronary artery calcification (CAC), its progression, and calcification biomarkers between patients on hemodia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 33 publications
0
13
1
Order By: Relevance
“…On the other hand, compared to the patients with end-stage renal disease (ESRD), especially those under maintenance hemodialysis, the degree of BWV should be modest in patients with predialysis CKD. Intriguingly, the progression of CAC in patients with ESRD is altered by the modality of renal replacement therapy ( 30 ). A recent observational study reported that peritoneal dialysis is not associated with CAC or is associated with less CAC progression than hemodialysis ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, compared to the patients with end-stage renal disease (ESRD), especially those under maintenance hemodialysis, the degree of BWV should be modest in patients with predialysis CKD. Intriguingly, the progression of CAC in patients with ESRD is altered by the modality of renal replacement therapy ( 30 ). A recent observational study reported that peritoneal dialysis is not associated with CAC or is associated with less CAC progression than hemodialysis ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, the progression of CAC in patients with ESRD is altered by the modality of renal replacement therapy ( 30 ). A recent observational study reported that peritoneal dialysis is not associated with CAC or is associated with less CAC progression than hemodialysis ( 30 ). Provided that BWV is inevitable in most patients on hemodialysis, rather than in patients on peritoneal dialysis, primarily due to the discontinuous nature of hemodialysis leading to saw-tooth volume fluctuations ( 31 ), it is speculated that BWV may also be representative of ongoing CAC progression in patients with ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional hemodialysis was the reference group. Of note, the comparison of CAC progression in conventional hemodialysis and peritoneal dialysis is discussed elsewhere [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…rences regarding the values of calcium, phosphorus and serum PTH in the 6 months prior to transplant, similar to some studies. published 23 where no differences are found regarding vascular calcification association, although there is controversy among various authors 24 .…”
Section: Originalsmentioning
confidence: 99%